Exploring the lived experience of individuals engaging in their own recovery process from drug addiction: A qualitative study - Avril, Kindo-Jermieson (The University of Edinburgh, 2011)
Objectives: Experimenting with drugs undoubtedly starts out as recreational. In spite of the risks and negative information with regard to taking drugs, people still feel the need to experiment. No-one deliberately sets out to become labelled as a ‘drug addict’. So what is the attraction? Previous research has identified a genetic basis for addiction and studies have explored aspects of the ‘self’ and ‘identity’ with regard to understanding addiction. In recent years, a multitude of studies comparing intervention, psychotherapies and maintenance programmes to treat addiction has been executed .The aim of this study was to explore participants own accounts of their lived experiences in engaging in their drug recovery. Design: The study uses Interpretive phenomenological analysis (IPA) to identify recurring themes by analysing participant’s experiences of drug addiction for a better understanding of the process of drug addiction, the defining moment of deciding to take back control and the recovery process. Methods: A qualitative research method was employed for this study. Six participants were recruited from a voluntary organisation in Scotland, which offers a free and confidential service to individuals whose lives have been affected by drug addiction. Using open questions, the semi-structured interviews took place at the centre. Data was recorded and transcribed verbatim. Data analysis followed IPA guidelines. Results: Participants described their experiences of becoming addicted, life as addicted and the process of recovery through their own engagement. The data analysis identified five superordinate themes: possessed; accounts of self; keeping busy; vicious cycle and avoiding endemic areas. Conclusions: The results are discussed in relation to current psychological literature for the identification of future intervention programmes and psychotherapies.
Keywords: Drug addiction; IPA; Recovery